Improved coalescence stability of monodisperse phospholipid-coated microbubbles formed by flow-focusing at elevated temperatures. Issue 1 (4th December 2018) - Segers, Tim; Lassus, Anne; Bussat, Philippe; Gaud, Emmanuel; Frinking, Peter
Abstract : The efficiency of phospholipids in monodisperse microbubble formation by flow focusing increases by 5 times at elevated temperatures. Abstract : Monodisperse phospholipid-coated ultrasound contrast agent (UCA) microbubbles can be directly synthesized in a lab-on-a-chip flow-focusing device. However, high total lipid concentrations are required to minimize on-chip bubble coalescence. Here, we characterize the coalescence probability and the long-term size stability of microbubbles formed using DPPC and DSPC based lipid mixtures as a function of temperature. We show that the coalescence probability can be dramatically reduced by increasing the temperature during bubble formation. Moreover, it is shown that the increased coalescence stability can be explained from an exponential increase of the relative viscosity in the thin liquid film between the colliding bubbles. Furthermore, it was found that the relative viscosity of a DPPC lipid mixture is 7.6 times higher than that of a DSPC mixture and that it can be explained solely from the higher DPPC liposome concentration. Regarding long-term bubble stability, the ratio of the initial on-chip bubble size to the final stable bubble size was always found to be 2.2 for DPPC and DSPC coated bubbles with 10 mol% DPPE-PEG5000, independent of the temperature. Moreover, it was demonstrated that the microbubble suspensions formed at elevated temperatures are highly stable over a time window of 2 to 4 days when collected in a vial. All in all, this work shows that, by increasing the temperature during bubble formation from room temperature to 70 °C, the efficiency of the use of phospholipids in microbubble formation by flow-focusing can be increased by 5 times.